2001
DOI: 10.1002/ajim.1052
|View full text |Cite
|
Sign up to set email alerts
|

A case‐control study of the relationship between the risk of colon cancer in men and exposures to occupational agents

Abstract: We have uncovered a number of occupational associations with colon cancer. For most of these agents, there are no published data to support or refute our observations. As there are few accepted risk factors for colon cancer, we suggest that new occupational and toxicologic studies be undertaken focusing on the more prevalent substances reported herein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
25
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 72 publications
5
25
0
1
Order By: Relevance
“…In agreement with our result, a meta-analysis reported that exposure to chromium was not associated with colon or rectal cancers 28. Exposure to iron oxide16 and lead29 was associated with rectal cancer but not with colon cancer.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In agreement with our result, a meta-analysis reported that exposure to chromium was not associated with colon or rectal cancers 28. Exposure to iron oxide16 and lead29 was associated with rectal cancer but not with colon cancer.…”
Section: Discussionsupporting
confidence: 92%
“…A population-based case–control study of men identified 21 chemical agents including polystyrene, mineral oils and hydrocarbon solvents that increased the risk of colorectal cancer 16. Industrial pollutants in the air and polycyclic aromatic hydrocarbons have also been associated with the development of colorectal cancer 2 17.…”
Section: Introductionmentioning
confidence: 99%
“…In this example, the cumulative lifetime risk of disease was doubled to 10%; this may be the case in selected occupational subgroups or in populations that have additional environmental risk factors for a particular disease. For example, Goldberg et al (2001) found that a number of industrial compounds were associated with colon cancer risk [25], and epidemiologic studies have long identified subpopulations defined by ethnicity and geography that have higher incidence rates (e.g., CRC rates in Hawaiian males of Japanese ethnicity [26]). The prevalence Table 6 Predictive validity of genetic testing for mutations in genes related to colorectal cancer (CRC) in an increased-risk population with frequent other causes of CRC (example 3) of the genetic marker remained the same as in the first example.…”
Section: Example 3 Genetic Testing In a Community/ Occupational Settmentioning
confidence: 99%
“…2,11,44 Some studies shown that higher incidence among the most sedentary compared to the most active occupations. 2,45,46 SOFT TISSUE SARCOMA Liver angiosarcoma is considered as a "signal" cancer of occupational etiology.…”
Section: Colorectal Cancermentioning
confidence: 99%